2023
DOI: 10.3390/jcm12072520
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Body Mass Composition on Outcome in Multiple Traumatized Patients—Results from the Fourth Thoracic and Third Lumbar Vertebrae: A Single-Center Retrospective Observational Study

Abstract: Background: Body mass composition (BC) was shown to correlate with outcome in patients after surgery and minor trauma. As BC is assessed using computed tomography (CT) and routinely applied in multiple trauma (MT), this study will help to analyze whether BC variables also correlate with outcome in trauma patients. Materials and Methods: Inclusion criteria were MT (Injury Severity Score (ISS) > 15) and whole-body CT (WBCT) scan on admission. Muscle and fat tissue were assessed at the level of the fourth thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, fat-free mass in the limbs does not correlate with that of the entire body [ 33 ]. Additionally, a recent study reported a significant association between SMI at the L3 level and survival in patients with multiple traumas but not with SMI at the T4 level [ 34 ]. Although previous studies have suggested strong correlations between total muscle mass and the L3, T4, and pectoralis muscles, caution should be exercised when determining the level of cross-sectional area to be used [ 20 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, fat-free mass in the limbs does not correlate with that of the entire body [ 33 ]. Additionally, a recent study reported a significant association between SMI at the L3 level and survival in patients with multiple traumas but not with SMI at the T4 level [ 34 ]. Although previous studies have suggested strong correlations between total muscle mass and the L3, T4, and pectoralis muscles, caution should be exercised when determining the level of cross-sectional area to be used [ 20 , 33 , 35 ].…”
Section: Discussionmentioning
confidence: 99%